Pendampingan Pajak Bagi Pelaku Usaha - Sari, Wa Ode Irma; Hasnita, Nita; Limbong, Diamond; Rachman, Sri Rachmawati (Ikatan Cendekiawan Muda Akuntansi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector that plays a vital role in the national economy. However, their contribution to tax revenue remains low due to limited tax literacy, administrative understanding, and technical skills. This study aims to enhance tax literacy and compliance among MSME actors in Kendari City through a community service program involving direct guidance. The activity was conducted face-to-face with 31 participants from various MSME sectors, including culinary, trade, services, and production. The approach combined theoretical instruction, practical training on filling out the Annual Tax Return (Form 1770), tax calculation simulations, and personalized guidance, supervised by students and faculty members. Evaluation was carried out using pre-tests and post-tests as well as participatory observation to assess improvements in understanding, technical skills, and tax reporting readiness. The results indicated significant improvement in participants’ comprehension of tax concepts, use of the DJP Online application, and ability to perform simple tax planning according to their business characteristics. The guidance also positively impacted the legality, credibility, and sustainability of MSME businesses while enhancing students’ soft skills, such as communication, practical mentoring, and systematic material delivery. These findings confirm that a combination of theory, practical exercises, and personal guidance is an effective strategy for improving MSME tax compliance. This activity can serve as a replicable model of community service in other regions to strengthen tax literacy, support small business administration, and increase MSMEs’ contribution to national revenue and local economic development.